Simulation and modelling of traffic movements at semi-actuated signalised intersections - Maria de Lurdes Oliveira Simões (2007)
This work presents a microscopic stochastic simulation model that emulates the traffic movements at signalised intersections with semi-actuated signal operation. Actuated regulations are governed by complex interactions between the signal control and the arrival of vehicles. The methodology developed in this work uses the car-following theory to describe the movement of each vehicle. We also describe the structure of the model and the steps that were followed for its implementation. A validation procedure was carried out using field data in a particular intersection. The impact of the green time, the yellow time and the red time assigned by the actuated system to each phase was also assessed. The relationship between simulated delays and the delays obtained from applying the Highway Capacity Manual (HCM) model was analysed. It indicates that simulated delays are higher than the delays given by the HCM which may be due to the characterisation of the vehicular movements and their interactions. The model outputs include measures of effectiveness such as total vehicular delay, average speed and average queue length.